Energy policy: European, national, regional? - Sebastian Strunz; Erik Gawel; Paul Lehmann; Teresa Ribera; Andreas Rüdinger; Ralf Boscheck; Christian Egenhofer; Jacques de Jong (Intereconomics, 2014)
When it comes to energy policy, EU countries go their own way with little regard for other member states. What strategies exist in the EU Commission to coordinate and integrate energy markets? Are these strategies consistent with national plans currently in action? Is it too late to establish a unified energy policy? What can be achieved in a unified energy policy given the considerable differences in resource endowment and political preferences in energy strategies? Can the effectiveness of EU energy policy objectives be enhanced through policy coordination at the regional scale? This Forum seeks to provide answers to these questions.
Keywords: 330; EU-Energiepolitik; Erneuerbare Energie; Nachhaltige Energieversorgung; Governance-Ansatz; Energiepolitik; EU-Staaten